2019
DOI: 10.12944/crnfsj.7.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Is Soft Drink Consumption Linked to Higher Body Mass Index and Energy Intake Among Adults in Mauritius?

Abstract: The World Health Organisation recommends people to keep their calorie intake from soft drink (SD) less than 10% of their daily calorie intake. Even though, calorie intake from soft drink consumption is low, there is an increase in the frequency of consumption. Also, besides, it is well understood that change in weight is not only dependent on soft drink consumption but also factors such as calorie intake and physical activity. The objective of this study is to investigate SD consumption and its association wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Body mass index (BMI) was derived from height and weight. BMI was treated as a binary variable and categorized into <25 kg/m 2 (non-overweight) and ≥25 kg/m 2 (overweight) [16]. Similarly, hypertension was also treated as a binary variable and categorized into a self-reported status of yes or no.…”
Section: Assessment Of Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…Body mass index (BMI) was derived from height and weight. BMI was treated as a binary variable and categorized into <25 kg/m 2 (non-overweight) and ≥25 kg/m 2 (overweight) [16]. Similarly, hypertension was also treated as a binary variable and categorized into a self-reported status of yes or no.…”
Section: Assessment Of Cardiometabolic Risk Factorsmentioning
confidence: 99%
“…40 Regarding beverage consumption (soft drinks and tea/coffee), the positive correlation between BMI reported in this study corresponds with a study on Mauritian women whereby higher intake of soft drinks resulted in high BMI. 3 Another study demonstrated that soft drink consumption was linked to an increased risk of abdominal obesity over a 10-year period. 41 However, in one study, consuming one or more portions of tea per day was linked to obesity, but the link was not statistically significant.…”
Section: Dietary Patterns/food Frequency Of the Female Older Adultsmentioning
confidence: 99%
“…2 Mauritius, an island nation, located in the southwest Indian Ocean, has a mixed economic system and is a multi-cultural and multi-ethnic country. 3 According to the Worldometers' elaboration of the most recent UN data, Mauritius' population is 1,275,555, as at 20 th April 2022 (https://www.worldometers.info/) 4 including 95,635 (https:// countrymeters.info/) people above 64 years old. 5 According to a national assessment of non-communicable diseases (NCDs) conducted in Mauritius in 2015, 19.1% of people were obese.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation